Life history traits and life table analysis of Lobiopa insularis (Coleoptera: Nitidulidae) fed on strawberry - Greco, Nancy Mabel (2017)
Lobiopa insularis is a newly reported pest of strawberry in Argentina. We investigated characteristics of its biology in the laboratory, including survivorship and reproduction. We also estimated population growth for L. insularis fed ripe strawberry fruits. Lobiopa insularis was not observed ovipositing on strawberry fruits. A higher proportion of egg masses were recorded from a depth of 1 cm within the soil than on either the soil surface or deeper than 1cm (i.e. between 1and 2 cm) within the soil. The duration of preimaginal developmental stages represented ∼18.5% of the total life cycle, while the adult stage represented 81.5%. Survival from egg to adult was 64.20% and mean longevity of females and males adults was 121.84, (SE = 8.86) and 118.58 (SE = 5.90) days, respectively. Females laid eggs only when they were with a male, so reproductive period was dependent on male presence. The number of eggs/female/day was 18.01 (SE = 1.71); and total fecundity was 1655 (ES = 249.53) eggs/female. The long life span of adults and high reproductive output, i.e high fecundity and long reproductive period, indicate that availability and concentration of suitable developmental resources are important factors in the population dynamics of Lobiopa insularis associated with strawberry crops.